Reflections on Viral Poetry “Paskah” on the Existence of Indonesian Religious Diversity - Achmad Muhajir Muhajir (Ilomata International Journal of Social Science, 2021)
Plurality is a necessity in life, especially in religious life. Toleransih or atsamuh which is embodied in the Medina Charter, is a teaching in the context of carrying out a hydrogen community life, especially in religion, so that there is peace in social life. The existence of a viral poem about "Easter" read by santri can be a polemic for religious life on the existence of religious diversity, especially in Indonesia. natural phenomena and human engineering. By explaining the concept of pluralism, it becomes a picture of togetherness in living a social and religious life with mutual respect and respect for each other.